Assessment of the relationship between environmental attributes and urban quality of life in, Malaysia - Roslan, Siti Nurul Munawwarah; Kari, Fatimah; Satar, Nurulhuda Mohd; Wan Abd Aziz, Wan Nor Azriyati (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Quality of life study has become an important issue among most of the researchers especially when it touches about urban living. There are many factors that significantly affect the quality of life and neighborhood satisfaction is one of the areas that concern many of the researches in the field of urbanism. Environment attributes are known as one of the factors that can affect neighborhood satisfaction. As the population is increasing rapidly in an urban area, it caused to increase in the unemployment crisis and amenities provided in urban areas. This study aims to evaluate the environmental attributes that can influence the urban resident's quality of life by adopting neighborhood satisfaction indicator as a mediator between the environmental attributes and quality of life. Primary data was collected in seven selected Klang Valley area through a survey involving 487 respondents for this study. SEM-AMOS was used for the data analysis. The findings revealed that there is partial mediation exist in the study that neighborhood satisfaction mediates the relationship between the environmental attributes and quality of life. © BEIESP.